FORMATION OF PROFESSIONAL COMPETENCE IN TEACHING A FOREIGN LANGUAGE - Najmeddinov Ahmad Rahmatovich (Galaxy International Interdisciplinary Research Journal, 2022)
Expansion of international relations and its acceptance in the international community has made a foreign language really relevant. The state and society began to experience a real need for people in practice, and often at the professional level, owning a foreign language. Free working knowledge of a foreign language was seen as a significant personal achievement. Foreign language to date to fully fulfill its original function as a means of communication means of initiation to another national culture, an important tool for the development of intellectual abilities of people.